Implementation Of Business Check Up For MSMEs Mapping In Indonesia - Paradisa Sukma; Victoria Kusumaningtyas Priyambodo; Eni Indriani (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this study is to assess the health of Mataram City's MSME enterprises. This is a descriptive quantitative study that employs radar analysis. A radar chart is a two-dimensional graph containing three or more quantitative variables shown on an axis beginning at the same position. This study employs 63 MSMEs as business review samples to examine the growth of seven characteristics of MSME enterprises, including independence, innovation, risk taking, marketing, operations, finance, and human resources. The application of radar analysis in performance evaluation or mapping of MSMEs in Mataram City leads to a positive outcome (radar 4-5). The independence component receives the greatest score, while the money aspect receives the lowest. Based on these findings, it is suggested that MSMEs enhance their financial performance. The findings of this study have consequences for the government in making policy decisions for the improvement and growth of MSMEs. Aside from that, the findings of this study have consequences for academics as a research reference for the present difficulties encountered by MSMEs and how to develop them further.